The impact of an empowerment evaluation professional development program on physical sciences teachers’ attitudes, beliefs and behavioral intentions to integrate ICT into their science lessons - Moosa, Sumayya; Ramnarain, Umesh (Frontiers in Education, 2023)
The purpose of this research study was to investigate and determine the impact of teacher’s attitudes and beliefs on their behavioural intentions to integrate ICT into their science lessons. and to establish the impact of a professional development programme underpinned by the principles of empowerment evaluation (EE) on their attitudes and beliefs. The participants were selected from five high schools in Johannesburg, South Africa. A validated questionnaire was used to identify teachers’ attitudes and beliefs and to measure the impact of their attitudes and beliefs on their behavioural intentions to integrate ICTs into their science lessons. The findings from this research study indicated that the empowerment evaluation approach positively impacted the teacher’s attitudes and beliefs as well as improved their behavioural intentions to integrate ICT into their science lessons. Furthermore, this study revealed that the more confident and competent a teacher felt to integrate ICT into his/her lessons, the more likely he/she would be able to integrate ICT into their lessons. Therefore, teachers’ behavioural intentions are important in predicting whether they will integrate ICT into their lessons.